Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.7763/ijesd.2015.v6.622
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Releasing Wastewater of Sugar Industries into Drainage System of LBOD, Sindh, Pakistan

Abstract: I. INTRODUCTION Water is important natural resource which covers 70% of earth that exists on planet of earth and without it, life cannot survive. The major human activities have been used for polluting fresh water bodies. About 1.5 billion people have no safe drinking water globally and about 5 million deaths per year are attributed due to waterborne diseases [1]. It is estimated that 70% of industrial wastes in developing countries are disposed of untreated into waters where they contaminate existing water su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…In addition, the studies reported that the coastal aquifers (southern Sindh) are overexploited; this may possibly lead to the saline intrusion, which increases Na and Cl concentrations in the coastal aquifers [46,47]. Elevated chloride in surface water contamination may be due to wastewater from industries (specifically sugar mills in South Sindh) and effluent from large drains in both zones (e.g., right bank outfall drainage and left bank outfall drainage) [46][47][48]. We were unable to find similar studies, but studies in similar geographic locations showed little variation in the chloride concentration in drinking water [40,49].…”
Section: Chloridementioning
confidence: 99%
“…In addition, the studies reported that the coastal aquifers (southern Sindh) are overexploited; this may possibly lead to the saline intrusion, which increases Na and Cl concentrations in the coastal aquifers [46,47]. Elevated chloride in surface water contamination may be due to wastewater from industries (specifically sugar mills in South Sindh) and effluent from large drains in both zones (e.g., right bank outfall drainage and left bank outfall drainage) [46][47][48]. We were unable to find similar studies, but studies in similar geographic locations showed little variation in the chloride concentration in drinking water [40,49].…”
Section: Chloridementioning
confidence: 99%
“…During the processing nearly 1000 L of wastewater is produced for every ton of cane crushed. High oxygen demand sugar industry waste water lead to the depletion of dissolved oxygen content in the water bodies if discharged untreated, resulting in rendering the water bodies unfit for both aquatic and human uses (Qureshi et al, 2015). If untreated wastewater is discharged on land, decaying organic solids present in the wastewater clog the soil pores (Reddy et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the increasing population is the main cause of the deterioration of surface and sub-surface water [15]. Major human activities have polluted fresh water sources [16]. In the future, global population growth is likely to occur mainly in the urban areas [17].…”
Section: Introductionmentioning
confidence: 99%